Cloud-based business services innovation: A risk management model. Issue 6 (December 2017) - Ali, Ali; Warren, Derrick; Mathiassen, Lars
Highlights: Literature synthesis covering the intersection of cloud-based business services, innovation, and risk management literature streams. Systematic, adaptive, and intuitive risk-strategy model to help cloud-based business services providers manage the risks involved. Adaptation and theoretical extension of McFarlan' (1981) portfolio approach to information-systems. Identification of services, technology, and process risk areas and exemplar risk items. Development of stakeholder engagement, technology development, innovation planning, and innovation control resolutions and exemplar actions. Abstract: Cloud computing providers and their software-as-a-service offerings have become more profuse and mature, making cloud technology an increasingly important platform for business services innovation. Although the cloud offers rich opportunities for transforming businesses—innovating existing services and introducing creative new ones—it also involves risks that business managers must identify and resolve to successfully drive innovation efforts. However, no comprehensive models are available to help managers assess and mitigate the risks they face. To address this void, we reviewed extant literature on cloud computing from a business innovation perspective to uncover the myriad challenges managers confront as they seek to leverage cloud technology in the ongoing transformation of their organization's service offerings. Combining this systematic literature analysis with relevant theory, we synthesized an integrated model for managing risk during innovation of cloud-based business services. The model identifies three types of risks (services, technology, and process risks) and four types of resolutions (stakeholder engagement, technology development, innovation planning, and innovation control). The model also helps managers identify their organization's general risk profile and link that profile to a specific configuration of resolutions.